1980
DOI: 10.1002/1097-0142(19800601)45:11<2880::aid-cncr2820451127>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and pathological study of adrenocortical carcinoma. Therapeutic implications

Abstract: Twenty-one patients with adrenocortical carcinoma (ACC) diagnosed at three hospitals over a ten-year period were reviewed for clinical and pathologic features that might have therapeutic implications.Depending upon the extent of cellular pleomorphism, ACC could be defined as anaplastic or differentiated. Anaplastic ACC occurred more often in male patients, produced more frequent cutaneous metastases ( P = 0.01), and was associated with a lack of clinical or laboratory evidence of hormone production ( P = 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 10 publications
2
36
0
1
Order By: Relevance
“…Tumour hyperfunctionality occurred in the majority of cases and manifested most commonly as Cushing syndrome. We did not find a relationship between tumour functionality and outcome, which despite the suggestions of some authors21 22 is consistent with the findings of most studies to date (see review 8). …”
Section: Discussionsupporting
confidence: 89%
“…Tumour hyperfunctionality occurred in the majority of cases and manifested most commonly as Cushing syndrome. We did not find a relationship between tumour functionality and outcome, which despite the suggestions of some authors21 22 is consistent with the findings of most studies to date (see review 8). …”
Section: Discussionsupporting
confidence: 89%
“…However, different clinical courses have been described among patients into the same tumor stage. Some retrospective analyses have reported that functional tumors may be associated with worse prognosis [30]. In addition, few studies have established histological or molecular markers, such as Ki67 index or TP53 mutations, as predictors of poor prognosis and its value still needs to be confirmed [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to symptoms from hormone excess, a palpable abdominal mass is the most common finding of adrenocortical carcinoma, with abdominal pain, weight loss, and fever also occurring frequently [8]. In the 1980s, Hogan et al [9] and Karakousis et al [10] suggested that functional tumors exhibited better prognosis than nonfunctional tumors. Functional status of tumors may alter time to diagnosis because nonfunctional tumors may not present until they reach large size and produce secondary symptoms from mass effect or metastatic disease [5].…”
Section: Presentationmentioning
confidence: 99%